Knockdown of hepatocyte Perilipin-3 mitigates hepatic steatosis and steatohepatitis caused by hepatocyte CGI-58 deletion in mice. (15th September 2022) - Bao, Xinyu; Ma, Xiaogen; Huang, Rongfeng; Chen, Jianghui; Xin, Haoran; Zhou, Meiyu; Li, Lihua; Tong, Shifei; Zhang, Qian; Shui, Guanghou; Deng, Fang; Yu, Liqing; et al.
ABSTRACT: Comparative gene identification-58 (CGI-58), also known as α/β hydrolase domain containing 5, is the co-activator of adipose triglyceride lipase that hydrolyzes triglycerides stored in the cytosolic lipid droplets. Mutations in CGI-58 gene cause Chanarin–Dorfman syndrome (CDS), an autosomal recessive neutral lipid storage disease with ichthyosis. The liver pathology of CDS manifests as steatosis and steatohepatitis, which currently has no effective treatments. Perilipin-3 (Plin3) is a member of the Perilipin–ADRP–TIP47 protein family that is essential for lipid droplet biogenesis. The objective of this study was to test a hypothesis that deletion of a major lipid droplet protein alleviates fatty liver pathogenesis caused by CGI-58 deficiency in hepatocytes. Adult CGI-58-floxed mice were injected with adeno-associated vectors simultaneously expressing the Cre recombinase and microRNA against Plin3 under the control of a hepatocyte-specific promoter, followed by high-fat diet feeding for 6 weeks. Liver and blood samples were then collected from these animals for histological and biochemical analysis. Plin3 knockdown in hepatocytes prevented steatosis, steatohepatitis, and necroptosis caused by hepatocyte CGI-58 deficiency. Our work is the first to show that inhibiting Plin3 in hepatocytes is sufficient to mitigate hepatocyte CGI-58 deficiency-induced hepatic steatosis and steatohepatitis in mice.